OPERATING OF MOBILE MACHINE UNITS SYSTEM USING THE MODEL OF MULTICOMPONENT COMPLEX MOVEMENT - Lebedev, A.; Artiomov, N.; Shulyak, M.; Podrigalo, M.; Abramov, D.; Klets, D.; Kaidalov, R.; Лебедев, А. Т.; Артёмов, Н. П.; Шуляк, М. Л.; Подригало, М. А.; Абрамов, Д. В.; et al. (Харьковский национальный автомобильно-дорожный университет, 2015)
To solve the problems of mobile machine units system operating it is proposed using complex multi-component (composite) movement physical models. Implementation of the proposed method is possible by creating of automatic operating systems of fuel supply to the engines using linear accelerometers. Some examples to illustrate the proposed method are offered.
УПРАВЛЕНИЕ СИСТЕМОЙ МОБИЛЬНЫХ МАШИННЫХ АГРЕГАТОВ С ИСПОЛЬЗОВАНИЕМ МОДЕЛИ МНОГОКОМПОНЕНТНОГО СЛОЖНОГО ДВИЖЕНИЯ
КЕРУВАННЯ СИСТЕМОЮ МОБІЛЬНИХ МАШИННИХ АГРЕГАТІВ З ВИКОРИСТАННЯМ МОДЕЛІ БАГАТОКОМПОНЕНТНОГО СКЛАДНОГО РУХУ
Keywords: machine unit; operating; multi-component complex motion; машинный агрегат; управление; многокомпонентное сложное движение; машинний агрегат; керування; багатокомпонентний складний рух; 629.017